The Flight Control of SHEFEX II - Scheuerpflug, Frank; Kallenbach, Alexander (ESA Communications, 2013)
SHEFEX II (Sharp Edge Flight Experiment) was a twostage sounding rocket mission to investigate advanced reentry technology. The successful launch was conducted from Andøya Rocket Range, Norway in June 2012. Comprising a suppressed trajectory, initiated by a cold-gas pointing maneuver prior to 2nd stage ignition, and spanning 800 km over the Norwegian sea, it was the most complex sounding rocket mission ever carried out by the German Aerospace Center DLR. To maximize the chances of a mission success, a mission scenario was developed that accounted for system failures and permitted to compensate for them or at least tolerate them long as no safety limits were infringed. The actual flight proved these measures very effective. A strong deviation of the unguided 1st stage from its nominal trajectory could be successfully compensated for by the flight control of the 2nd stage. This resulted in a nominal mission sequence and payload impact in immediate proximity of the nominal aiming point.